Penguatan Kepemimpinan dan Manajemen Organisasi melalui Kegiatan Diklatsar Mahasiswa Pecinta Alam Universitas Bina Bangsa - Asep Rahmatullah; Galuh Mulyawan; Hadi Kurniawanto; Try Adhi Bangsawan; Muhammad Angga Anggriawan (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Student organizations play a strategic role in developing students' character, leadership, and managerial competencies. The Student Nature Lovers Association of Universitas Bina Bangsa (MAPELBA), as a high-achieving student organization, requires strong leadership and organizational management to sustain its performance and achievements. A needs assessment revealed limited understanding of organizational leadership, unsystematic work program planning, and suboptimal administrative and financial management. This community service program aimed to strengthen leadership and organizational management capacity through a Basic Education and Training (Diklatsar) program involving 14 participants. A participatory, educational, and practical approach was implemented through needs assessment, module development, interactive training, discussions, leadership simulations, role-playing, and workshops. The program improved participants' understanding of leadership, organizational roles, work program planning, communication, teamwork, and systematic administration, thereby supporting more professional, accountable, and sustainable organizational governance.